An outbreak of Salmonella Enteritidis phage type 34a infection associated with a Chinese restaurant in Suffolk, United Kingdom - Mahgoub Hamid; Sundkvist Torbjorn; Badrinath Padmanabhan; Kent Richard (BMC, 2004)
Abstract Background On 30th July 2002, the Suffolk Communicable Disease Control Team received notifications of gastrointestinal illness due to Salmonella Enteritidis in subjects who had eaten food from a Chinese restaurant on 27th July. An Outbreak Control Team was formed resulting in extensive epidemiological, microbiological and environmental investigations. Methods Attempts were made to contact everybody who ate food from the restaurant on 27th July and a standard case definition was adopted. Using a pre-designed proforma information was gathered from both sick and well subjects. Food specific attack rates were calculated and two-tailed Fisher's exact test was used to test the difference between type of food consumed and the health status. Using a retrospective cohort design univariate Relative Risks and 95% Confidence Intervals were calculated for specific food items. Results Data was gathered on 52 people of whom 38 developed gastrointestinal symptoms; 16 male and 22 female. The mean age was 27 years. The mean incubation period was 30 hours with a range of 6 to 90 hours. Food attack rates were significantly higher for egg, special and chicken fried rice. Relative risk and the Confidence interval for these food items were 1.97 (1.11-3.48), 1.56 (1.23-1.97) and 1.48 (1.20-1.83) respectively. Interviews with the chef revealed that many eggs were used in the preparation of egg-fried rice, which was left at room temperature for seven hours and was used in the preparation of the other two rice dishes. Of the 31 submitted stool specimens 28 tested positive for S Enteritidis phage type 34a and one for S Enteritidis phage type 4. Conclusion In the absence of left over food available for microbiological examination, epidemiological investigation strongly suggested the eggs used in the preparation of the egg-fried rice as the vehicle for this outbreak. This investigation highlights the importance of safe practices in cooking and handling of eggs in restaurants.